Preliminary Study of the Fruit Body Formation of Lentinus polychrous Lev. - Thipprasert, Wichet; Norarat, Rattanaporn; Wannachai, Somsak; maneesran, Nattawat; Jenpanutsak, Santisuk (Journal of Advanced Development in Engineering and Science, 2023)
This study aims to investigate the optimal voltage for stimulating the fruit body formation of Lentinus polychrous Lev. by using high voltage generator. There are 2 treatments for the fruit body formation of Lentinus polychrous Lev. including: the treatment without stimulation (control group) and the treatment with high voltage stimulation in the range of 20 – 50 kV for 10 seconds. After stimulation, mushrooms were kept in a controlled mushroom farm recording temperature and humidity by using a data logger. After collecting mushrooms for 35 days, we found that the total weight of mushroom applied with 50 kV for 10 seconds is higher than that of control group for 1.48 times. However, the repeat experiment is necessary to obtain reliable data.